Association between the examination rate of treatment‐resistant schizophrenia and the clozapine prescription rate in a nationwide dissemination and implementation study. Issue 1 (2nd December 2021) - Yasui‐Furukori, Norio; Muraoka, Hiroyuki; Hasegawa, Naomi; Ochi, Shinichiro; Numata, Shusuke; Hori, Hikaru; Hishimoto, Akitoyo; Onitsuka, Toshiaki; Ohi, Kazutaka; Hashimoto, Naoki; Nagasawa, Tatsuya; Takaesu, Yoshikazu; et al.
Abstract: Background: The decision to initiate clozapine treatment should be made on an individual basis and may be closely related to the early detection of treatment‐resistant schizophrenia (TRS), although there is evidence that the early use of clozapine results in a better response to treatment. Therefore, we investigated the relationship between the examination rate of TRS and the prescription rate of clozapine. Methods: After attending a 1‐day educational program on schizophrenia based on the "Guidelines for the Pharmacological Treatment of Schizophrenia, " we asked the participating facilities to submit records of whether or not TRS was evaluated for each patient. We calculated the clozapine prescription rate from the schizophrenic patients prescribed clozapine and all of the schizophrenic patients. Forty‐nine facilities in 2017 were included in the study. Results: There were dichotomous distributions in the examination rate of TRS and a non‐normal distribution in the prescription rate of clozapine. There was a significant correlation between the prescription rate of clozapine and the examination rate of TRS ( r s  = 0.531, P  = 1.032 × 10 −4 ). A significant difference was found in the prescription rate of clozapine between the three groups of facilities according to the examination rate of TRS. Conclusion: As a preliminary problem for the use of clozapine, in Japan, the examination rate of TRS varies, and there are many facilities that typically do not consider the possibility of TRS; this trend leads to a low rate of clozapine use. Clearly, further clinician training is needed for the early detection and appropriate management of TRS that includes an explanation of TRS and how to introduce clozapine therapy to patients and their families. Abstract : A significant difference was found ( P  = .041) in the prescription rate of clozapine between the three groups according to the examination rate of TRS. Post hoc analysis revealed that the prescription rate of clozapine in facilities with a high examination rate ( P  = .014) was significantly higher than that in facilities with a low examination rate of TRS.